ANALYSIS THE EFFECT OF LEARNING DIFFICULTIES ON CHEMISTRY STUDENTS LEARNING ACHIEVEMENT AT CLASS XI IN MAN 4 MALUKU TENGAH - RISNAWATI (PARADIGMA: Jurnal Ilmu Pendidikan dan Humaniora, 2024)
This study aims to determine the factors behind learning difficulties that have an impact on student achievement in chemistry subjects. The subjects in this study were students of class XI IPA Madrasah Aliyah Negeri 4 Central Maluku located in Rajawali village, Banda District, Central Maluku Regency, Maluku Province were totaling 27 people. This type of research is included in descriptive research with a qualitative approach. From the UAS results for the 2022/2023 academic year, the average grade of student at class XI IPA MAN 4 Central Maluku in chemistry subjects was 64.6 with the highest score is 80 and the lowest score is 40. The recap of the test results shows that about 70.4% of students achievement is low. To collect information about learning difficulties experienced by students, researchers used indirect communication techniques using data collection tools in the form of research questionnaires with 30 questions. Based on the results of a questionnaire from 27 respondents in class XI IPA MAN 4 Central Maluku, it shows that there are some different levels of difficulty in learning difficulties experienced by students. Based on the existing indicators obtained 4 students with a percentage of 15%, indicating that the level of difficulty with a medium standard. 7 students with a percentage of 26% which means they have a level of difficulty with a sufficient standard. 14 students with a percentage of 52% and shows the level of difficulty with a standard that is less. 2 students with a percentage of 7%, showing the level of difficulty with a very low standard. The difference of student’s abilities of learning is the cause how low achievement of student learning outcomes in class XI IPA MAN 4 Central Maluku. Taken as a whole, it can be seen that the learning difficulties experienced by students in teaching and learning activities greatly affect the achievement of their learning outcomes.